2017
DOI: 10.1371/journal.pgen.1006820
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Sjögren's syndrome susceptibility locus at OAS1 that influences isoform switching, protein expression, and responsiveness to type I interferons

Abstract: Sjögren’s syndrome (SS) is a common, autoimmune exocrinopathy distinguished by keratoconjunctivitis sicca and xerostomia. Patients frequently develop serious complications including lymphoma, pulmonary dysfunction, neuropathy, vasculitis, and debilitating fatigue. Dysregulation of type I interferon (IFN) pathway is a prominent feature of SS and is correlated with increased autoantibody titers and disease severity. To identify genetic determinants of IFN pathway dysregulation in SS, we performed cis-expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 112 publications
3
65
0
Order By: Relevance
“…While p42, p46, and p48 are robustly expressed, p44 and p52 protein levels are significantly decreased ( Figure 3B). Consistent with our results, a previous study failed to detect endogenous p44 and p52 isoforms in primary human cells 33 . To ensure the lack of RNase L activation is due to lowered expression, we directly tested enzymatic activity in vitro using equimolar amounts of full length purified protein ( Figure S3B).…”
Section: Variation In Human Oas1 Activity Reflects Altered Isoform Stsupporting
confidence: 93%
See 1 more Smart Citation
“…While p42, p46, and p48 are robustly expressed, p44 and p52 protein levels are significantly decreased ( Figure 3B). Consistent with our results, a previous study failed to detect endogenous p44 and p52 isoforms in primary human cells 33 . To ensure the lack of RNase L activation is due to lowered expression, we directly tested enzymatic activity in vitro using equimolar amounts of full length purified protein ( Figure S3B).…”
Section: Variation In Human Oas1 Activity Reflects Altered Isoform Stsupporting
confidence: 93%
“…In some cases, common genetic variants in key mediators of cellular immunity lead to partial or complete loss of protein function and can also be associated with disease. The human OAS1 variant associated with lower in vivo 2-5A levels is also associated with increased risk of infection with West Nile virus 44 and development of Sjörgens syndrome 33 , an autoimmune disease associated EBV and CMV infection. Despite these risks, the allele resulting in production of unstable OAS1 isoforms rose to near fixation in ancient African populations, proceeded by reintroduction of the ancestral high activity allele via introgression from Neandertals to non-African populations [45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, comparison of the expression efficiencies of different hOAS1 isoforms indicated that the p42 and p46 isoforms were expressed at much higher levels in HEK293 cells than the other isoforms tested, suggesting that these two isoforms may have a higher stability in a mammalian cell. A recent study also showed that p44 and p48 were expressed at lower levels compared to p42 and p46 after transfection of HEK 293 cells, even though the mRNA levels for all of the isoforms were similar [24]. Sequential truncation of the C-terminal ends of p44 and p48 resulted in increased expression levels, indicating that the C-terminal regions are responsible for the decreased stability of these two isoforms.…”
Section: Discussionmentioning
confidence: 95%
“…In another study, although the transcript levels for Xpress tagged p42, p44, p46 and p48 were equivalent in HEK 293T cells after 48 h of expression, p44 and p48 had impaired protein expression compared to p42 and p46. Also, only endogenous p42, p46 and p48 were detected at the protein level in non-transfected cells [24]. To analyze isoform-specific synthetase activity, HEK293 cells were transfected with an hOAS1 isoform cDNA (1 µg of plasmid DNA) and 24 h later, cells were either mock-or poly(I:C)-transfected for 6 h. Total intracellular RNA was then extracted and separated on a denaturing agarose gel to detect cellular rRNA cleavage by activated RNase L. Surprisingly, the most efficiently expressed isoforms (p42 and p46) both activated RNase L cleavage, as indicated by the additional bands detected below the 18S and 28S rRNA bands in the absence of poly(I:C) transfection ( Figure 3B).…”
Section: The Hoas1 P42 P44 P46 P48 and P52 Isoforms Are Functionalmentioning
confidence: 96%
“…For example, evidence indicates reduced glycosylation and alterations in sialylation or sulfation of secreted salivary MUC5B and MUC7 in pSS patients (Alliende et al, 2008;Chaudhury, Proctor, Karlsson, Carpenter, & Flowers, 2016). Additionally, altered RNA splicing in pSS (Li et al, 2017) may produce MAM isoforms with reduced Ser/Thr-rich tandem repeats, decreasing potential glycosylation sites. It is well established that MAM expression, in vitro, can be altered in response to inflammatory cytokines (Dhanisha, Guruvayoorappan, Drishya, & Abeesh, 2018).…”
Section: Changes In the Levels Of Mam Transcripts Associated With Pssmentioning
confidence: 99%